Keragaman Jamur Tanah pada Pertanaman Ubi Kayu (Manihot Esculenta) di Kecamatan Sematang Borang Palembang - Haperidah Nunilahwati; Laili Nisfuriah; Bayu Ramadhannu (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Nunilahwati H, Nisfuriah L, Ramadhannu B. 2021. Diversity of soil fungi on cassava (Manihot Esculenta) plantation in sematang Borang Regency, Palembang. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 180-185. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Soil fungi are commonly found around the rhizosphere in plantations. This study aims to determine the diversity of soil fungi on cassava plants in Sematang Borang District, Palembang City. The research started from March to May 2020 at the Pest and Disease Plants Laboratory, Faculty of Agriculture, University of Palembang. The implementation of the research began with purposive sampling of soil samples on the rhizosphere of cassava plantations. The insect bait method uses Omphisa fuscidentalis larvae as bait to get soil fungi in the rhizosphere of cassava plants. Observations were made macroscopically and microscopically on infected bait insect larvae and on culture on PDA media. The soil fungi found were then identified. The results found 5 genera of soil fungi, namely Aspergillus sp, Penicillium sp, Beauveria sp, Trichoderma sp, and Fusarium sp. The soil fungi found were entomopathogenic fungi and pathogenic fungi.